2015
DOI: 10.1080/15384101.2015.1090065
|View full text |Cite|
|
Sign up to set email alerts
|

Novel phase I study combining G1 phase, S phase, and G2/M phase cell cycle inhibitors in patients with advanced malignancies

Abstract: PURPOSE:Cancer is a manifestation of aberrant cellular proliferation, and the cell cycle is one of the most successfully drugged targets in oncology. No prior study has been reported that simultaneously targets the 3 principal cell cycle phases populated by proliferating cells -G 1 , S, and G 2 /M.METHODS: Temsirolimus (G 1 inhibitor), topotecan (S inhibitor), and bortezomib (G 2 /M inhibitor) were administered in combination to patients with advanced malignancies using a 3+3 dose escalation schedule to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The G0 phase refers to the resting cells which are outside the cell cycle and are not affected by chemotherapy 19,20 . The G0 phase of cells does not express Ki‐67 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The G0 phase refers to the resting cells which are outside the cell cycle and are not affected by chemotherapy 19,20 . The G0 phase of cells does not express Ki‐67 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The G0 phase refers to the resting cells which are outside the cell cycle and are not affected by chemotherapy. 19,20 The G0 phase of cells does not express Ki-67. 21 We wanted to know whether the suppression of the cell cycle after TDT knockout was associated with more G0 phase cells which finally led to drug resistance.…”
Section: Deletion Of Tdt Slows Down Proliferation Arrests the Cell Cy...mentioning
confidence: 99%
“…In a phase II trial, all patients with thyroid cancer, except one with ATC, experienced stable disease, or partial response on the combination of temsirolimus and sorafenib ( 27 ). In another phase I trial, patients with PTC and FTC remained without progression longer than a year with temsirolimus, topotecan, and bortezomib treatment ( 24 ). A recent study using patient-derived xenograft mouse models of oncocytic carcinoma of the thyroid (OCA) with upregulated mTOR signaling showed tumor suppressing effect of mTOR inhibitors for both primary tumor and metastasis ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7 clinical trials, three retrospectives, one case report, and one preliminary report were found through a literature search using PubMed (National Library of Medicine, Bethesda, MD, USA). In total, eight clinical trials and one retrospective study are analyzed and described in Table 1 (23)(24)(25)(26)(27)(28)(29)(30)(31). One case report and one retrospective study were excluded from the table as their patients overlapped with the clinical trials (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…Here we see that TOP1 inhibition modulates different genes in parental and BRAFi/MEKi-resistant cells through our RPPA analysis. In parental cells, Topotecan modulates pathways related to proteins included in the response of DNA damage and stress, that are the known mechanisms of action for Topotecan (69)(70)(71), whereas, in BRAFi/MEKi-resistant cells, Topotecan upregulates different metabolic processes and downregulates the metalloproteinases 2 and 9 that are particularly important in the invasion process.…”
Section: Discussionmentioning
confidence: 99%